Pengaruh Budaya Organisasi dan Persepsi Lingkungan Kerja terhadap Loyalitas Kerja dengan Kepuasan Kerja sebagai Variabel Intervening pada PT Dharma Satya Nusantara Group Muara Wahau Kalimantan Timur - Ridadamai Setianingrum; Hardani Widhiastuti; Rusmalia Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of organizational culture and perceptions of the work environment on the work loyalty of PT Dharma Satya Nusantara Group employees, with job satisfaction as an intervening variable. This research was motivated by the gap between the initial questionnaire data which indicated a high level of work loyalty, and the interview results which indicated the existence of employees with low loyalty. The research method used is quantitative, with data collection through questionnaires and interviews. The research sample was 114 employees of PT Dharma Satya Nusantara Group. Data analysis was carried out using multiple regression analysis. SmartPLS 4.0. The research results show that: 1: Organizational culture influences job satisfaction 2: Perception of the Work Environment influences Job Satisfaction 3: Job Satisfaction influences Job Loyalty 4: Perception of the Work Environment influences Job Loyalty 5: Organizational culture influences work loyalty 6: The influence of organizational culture and job satisfaction on job loyalty 7: There is an influence of Work Environment Perception and Job Satisfaction on Job Loyalty The implication of this research is that it is important for companies to pay attention to organizational culture and create a positive work environment to increase employee job satisfaction, which will ultimately have an impact on increasing work loyalty.